An Empirical Analysis of Higher Education and Economic Growth in India - Olwin M. DSouza, Sonal Steevan Lobo (Journal of Informatics Education and Research, 2024)
This paper analyses the relationship between education and economic growth in India. It makes a contribution to the literature by analyzing the existence of nonlinearities in this relationship. The direction of the causality that we account for is from education to economic growth. In some cases, an increase in education might have a positive (or large) effect on GDP growth and, in other cases, the effect might be negative (or small). Because the effect of education might differ in different stages, nonlinearities gain importance in the analysis of the relationship between education and economic growth. Specifically, we hypothesise that a country’s economic growth performance differs depending on the evolution of its human capital and hence, on its educational achievement. Additional we have made an attempt to relate the population data with the economic growth, the results reveals that the influence of population growth has less relation with respect to economic growth. The results proved that the education and per capital income have direct positive relationship with the economic growth.